Metaphors of Faith: Exploring Spiritual Journey through Concrete Analogies in Nick Vujicic's Works - Meidhiatiningsih, Amelia; Muhamadi , Sani Insan (JETLEE : Journal of English Language Teaching, Linguistics, and Literature, 2024)
The concept of belief stands as a cornerstone in religion, shaping personal identities and worldviews. Nick Vujicic, born with Tetra-amelia syndrome, exemplifies how profound faith can empower individuals. His journey from early familial challenges to becoming a renowned motivational speaker and evangelist is rooted in his unwavering belief in God. Vujicic's expressions of faith, documented in his writings, provide a compelling case for exploring how conceptual metaphor theory illuminates his understanding and communication of faith-related experiences. This theory suggests that metaphors structure cognition by linking abstract ideas to concrete domains, offering insights into how religious beliefs are internalized and conveyed. The aims of this study are to describe and analyze the conceptual metaphors which occur from the words “faith” in the book Be the Hands and Feet: Living Out God’s Love for All His Children, and to describe and analyze the image schema transformation from the word “faith” in the books. The research employs a descriptive qualitative method to explore the conceptual metaphors of "faith" within Nick Vujicic's books. The methodology involves searching and exploring textual passages that discuss "faith," followed by detailed analysis and classification of conceptual metaphors—specifically, ontological, structural, and orientational metaphors—identified within the text. The results of this study the author found four metaphors, namely faith is a vehicle, faith is a building, faith is a human, and faith is a journey.